2018
DOI: 10.1039/c8dt00716k
|View full text |Cite
|
Sign up to set email alerts
|

DNA interactions of non-chelating tinidazole-based coordination compounds and their structural, redox and cytotoxic properties

Abstract: Novel tinidazole (tnz) coordination compounds of different geometries were synthesised, whose respective solid-state packing appears to be driven by inter- and intramolecular lone pairπ interactions. The copper(ii) compounds exhibit interesting redox properties originating from both the tnz and the metal ions. These complexes interact with DNA through two distinct ways, namely via electrostatic interactions or/and groove binding, and they can mediate the generation of ROS that damage the biomolecule. Cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Based on our results that suggest an increase of ROS in FLC-treated cells, we hypothesized that treatment with FLC leads to chromosomal instability through the mechanism that involves ROS. Previous studies have indicated that antimicrobial drugs can couple with metals and form metal complexes that potentiate DNA damage [39] Coordination of FLC to copper and iron in aqueous solution was confirmed using MALDI-TOF mass spectrometry (Table B and Figure D in S1 File). For both Fe II and Cu II , two equivalents of FLC bound per metal ion.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Based on our results that suggest an increase of ROS in FLC-treated cells, we hypothesized that treatment with FLC leads to chromosomal instability through the mechanism that involves ROS. Previous studies have indicated that antimicrobial drugs can couple with metals and form metal complexes that potentiate DNA damage [39] Coordination of FLC to copper and iron in aqueous solution was confirmed using MALDI-TOF mass spectrometry (Table B and Figure D in S1 File). For both Fe II and Cu II , two equivalents of FLC bound per metal ion.…”
Section: Resultsmentioning
confidence: 70%
“…DNA damaging effects of phenolic compounds mediated by iron and copper have been reported, supporting the idea that DNA damage caused by FLC in vitro is also mediated by coordinated metals [5961]. Previous studies have demonstrated DNA damage in vitro by imidazole-based compounds complexed with metals [39, 62]. Chemotherapeutic agents may cause direct DNA damage through agent-DNA binding and indirect damage through inhibition of DNA repair or accumulation of intracellular ROS [63].…”
Section: Discussionmentioning
confidence: 85%
“…It was observed a shifting of the copper( ii ) d–d electronic transition to higher energies as expected when substituting the halide atoms for the water molecules. 14 Thus, the halides were substituted by water molecules and the resulting [Cu(H 2 O) 2 (tnz) 2 ] 2+ complexes were used for the molecular dynamics. Table S2† shows energetic values for the optimized molecules with tnz ligands and halides or water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the descriptors and QSAR models were computed with the program CODESSA 34 using a Multiple Linear Regression (MLR) statistical procedure that relates any atomic property with the redox potential of the change Cu II /Cu I ( E 1/2 ) (values taken from ref. 14 and 33). Once calculated, tested, and validated, the best model was used to calculate the redox potential in the three most stable adducts generated by the interaction between the tinidazole-based complexes and DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation